The Importance of Improving the Performance of Kampung Performance on Community Services at Kalisusu Office, Nabire District - Petrus Mangambe (Budapest International Research and Critics University, 2022)
In Development Planning in Dagouto Village, Paniai Timur District, Paniai Regency